Rooting for a Serbian-Dominated Yugoslavia? The United Kingdom and the Recognition of Slovenia and Croatia - Methfessel Christian (Comparative Southeast European Studies)
The recognition of Slovenia and Croatia was a defining moment in the history of the post-Cold War order in Europe. From the outset, this step was a controversial one, and scholars focussing on the role of the United Kingdom often claim that London’s responses to the collapse of Yugoslavia can be explained by a long British tradition of pro-Serbian sentiment, the Foreign Office’s realpolitik approach, or Britain’s neocolonial interests. This article analyses British foreign policy on the basis of recently declassified documents in order to critically discuss such assumptions about the motives of British foreign policy and thus contribute to the international history of the Yugoslav Wars in the early 1990s.